Characteristics and outcome of acute heart failure patients according to the severity of peripheral oedema. (15th June 2019) - Shoaib, Ahmad; Mamas, Mamas A.; Ahmad, Qazi S.; McDonagh, Theresa M.; Hardman, Suzanna M.C.; Rashid, Muhammad; Butler, Robert; Duckett, Simon; Satchithananda, Duwarakan; Nolan, James; Dargie, Henry J.; Clark, Andrew L.; et al.
Abstract: Background: Most trials of patients hospitalized for heart failure focus on breathlessness (alveolar pulmonary oedema) but worsening peripheral oedema is also an important presentation. We investigated the relationship between the severity of peripheral oedema on admission and outcome amongst patients with a primary discharge death or diagnosis of heart failure. Objectives: We tested the hypothesis that severity of peripheral oedema is associated with length of hospital stay and mortality. Methods: Patient variables reported to the National Heart Failure Audit for England & Wales between April 2008 and March 2013 were included in this analysis. Peripheral oedema was classified as 'none', 'mild', 'moderate' or 'severe'. Length of stay, mortality during the index admission and for up to three years after discharge are reported. Results: Of 121, 214 patients, peripheral oedema on admission was absent in 24%, mild in 24%, moderate in 33% and severe in 18%. Median length of stay was, respectively, 6, 7, 9 and 12 days (P- < 0.001), index admission mortality was 7%, 8%, 10% and 16% (P- < 0.001) and mortality at a median follow-up of 344 (IQR 94–766) days was 39%, 46%, 52% and 59%. In an adjusted multi-variable Cox model, the hazard ratio for death was 1.51 for severe (P- < 0.001, CI 1.50–1.53), 1.21 for moderate (P- < 0.001, CI 1.20–1.22) and 1.04 (P- < 0.001, CI 1.02–1.05) for mild peripheral oedema compared to patients without peripheral oedema at presentation. Conclusion: Length of hospital stay and mortality during index admission and after discharge increased progressively with increasing severity of peripheral oedema at admission. Highlights: Most studies of 'acute' heart failure focus on breathlessness but peripheral oedema might be important. In this study, patients with severe peripheral oedema have prolonged hospital stays and a poor prognosis. This analysis provides the rationale for designing trials with peripheral oedema as the primary therapeutic target.